A study of two-phase annular flow using unsteady numerical computations. (May 2020) - Saxena, Abhishek; Prasser, Horst-Michael
Abstract: Flow behavior of thin liquid films in an annular flow regime is an important element of the thermal hydraulics of a BWR – it controls the heat transfer from the fuel rods to the coolant. Despite its relevance, the flow behavior of dynamic liquid films is not well understood even in adiabatic conditions. To investigate it, unsteady numerical simulations with an interface tracking model were performed in a double subchannel geometry with a P / D ratio of 1.325. Different turbulence models, namely the large eddy simulation (LES) and linear/nonlinear eddy viscosity unsteady-RANS (URANS) models, were tested. A novel approach for generating turbulent inlet conditions in a periodic flow domain was developed to reduce computational efforts. Validation against experimental data revealed shortcomings of the linear eddy-viscosity RANS model in predicting key flow parameters. By capturing the effects of the secondary flow structures in a subchannel geometry, improved predictions were obtained with a non-linear SST k – ω (QCR) turbulence model. Time-averaged liquid film thickness (LFT) and tracer distribution obtained with LES were found to have the best agreement with experimental data. Instantaneous and time-averaged velocity profiles were analyzed to understand the influence of the gas-liquid interface. Secondary flow structures in the subchannel gap region were found to enhance the turbulent mixing of the passive scalar in the liquid film. This finding is relevant towards the prediction of thermal-hydraulic parameters in a multichannel flow assembly by accounting for inter-channel mixing phenomena.